THE INFLUENCE OF PRE SEEDING SEEDS’ TREATMENT LEGUME COMPONENT ON THE SHOOTS’ DENSITY OF ALFALFA- CEREAL AGROPHYTOCENOSES - Ковтун, К. П.; Сеник, І. І.; Сидорук, Г. П.; Сеник, Р. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The purpose of research is to study the issue of pre seeding treatment of legume component seed on the density formation of shoots seeded meadow alfalfa- cereal grass stand. Methods. Laboratory and field experience were conducted which studied the concentration of growth promoters and different ways of pre seeding treatment legume component seed based on the research purpose. We studied followingvariants in the laboratory experience: 1. Control; 2. Growth Stimulator Viva 100ml / t; 3. Growth Stimulator Viva 200ml / t; 4. Growth Stimulator Viva 300 ml / t; 5. Growth Stimulator Viva 400ml / t; 6.Growth Stimulator Viva 500ml / t We studied following variants in the field experiment: 1. Control without processing 2. Processing of seed by growth stimulator; 3. Processing of seed by Rizobofit; 4. Processing of seeds by growth stimulator and Rizobofit. Results. The most optimal is 2% concentration of growth stimulator Viva in composition from studied us concentrations, as there was a significant increase of laboratory germination seed and fresh weight seedling 4.2% and 0.7337 g., respectively in this variant. The greatest number of legume sprouts fixed at the variant a joint application of growth stimulator Viva and bacterial product Rizobofit for pre seeding treatment of seed - 600 pcs. m2,as a valuable component of the grass stand, that more control on 77 pcs., variants with an independent use of growth stimulator and bacterial product provide results at level 591 and 578 pcs. / m2, respectively.The high-density of shoots scored variant with a combination of the growth use of stimulator Viva and bacterial product Rizobofit - 1492 pcs. / m2 in the two years’ average use seeded meadow agrophytocenoses among the studied methods of pre seeding treatment of legume component seed. Alfalfa occupied 503 pcs. / m2, tall fescue - 881 pcs. / m2, brome - 108 pcs. / m2. Discussion. The laboratory and field studies indicate the feasibility of the use of growth-rooting stimulators with properties of antistress agent in technologies create seeded meadow agrophytocenoses. It promotes the formation of a dense grassstand with a high content of commercially valuable components and long storage in it legume grasses. Indicated line of research requires continuous learning and improvement considering that agriculturalchemicals market are constantly emerging new products